Effect of decomposition temperature on crystallite size and strain for alumina - K.Saeed, Ghazi; A.Abass , Sattar (University of Thi-Qar Journal, 2019)
The crystallite size and strain of Al2O3 ceramic powder have been determined from x-ray line-broadening analysis at different decomposition temperatures. The Al2O3 powder have been prepared from decomposition of aluminum hydroxide Al(OH)3 at different temperature which have been characterized by X-Ray diffraction (XRD) and Differential, Thermal Analysis (DTA) methods. Deconvolution of the experimental profiles by Fourier cosine coefficients has resulted in corrected values of crystallite size. The crystallite size has been found to increase with increasing decomposition temperature from 38nm at 1673k to 73nm at 1873k. Strain on the other hand decrease from 3.04×10-3 at 1673k to 1.14×10-3 at 1873k. Estimation of micro hardness on compacts of different crystallite size has shown that crystallite size may influence the bearing load that compact can endure.